Differential Regulation of Platelet Aggregation by Matrix Metalloproteinases-9 and -2 - Fernandez-Patron, Carlos; Martinez-Cuesta, Maria A.; Salas, Eduardo; Sawicki, Grzegorz; Wozniak, Mieczyslaw; Radomski, Marek W.; Davidge, Sandra T. (Thrombosis and Haemostasis, 1999)
We have recently found matrix metalloproteinase-2 (MMP-2) in human platelets and reported that the release of this enzyme during platelet activation stimulates aggregation. We have now identified matrix metalloproteinase-9 (MMP-9) in human platelets and resistance-sized (~200 μm) arteries. Resting platelets released small quantities of pro-MMP-9. Maximal release of MMP-9 was detected during partial (appr. 30% maximum) aggregation with thrombin. However, maximal release of MMP-2 was associated with maximal aggregation. MMP-9 antibodies induced aggregation of resting platelets and potentiated aggregation of platelets induced by thrombin and collagen. Moreover, MMP-9 microisolated from arteries as well as recombinant human MMP-9 (0.1-30 ng/ml) inhibited thrombin and collagen-induced aggregation. We conclude that MMP-9 is an inhibitor of aggregation and in this action opposes the effects of MMP-2. The MMP-2/MMP-9 system may play an important role in the regulation of platelet-platelet and platelet-vessel wall interactions.
Keywords: MMPs; vascular; platelets; aggregation